A cash plus program reduces youth exposure to physical violence in Zimbabwe. (October 2020) - Chakrabarti, Averi; Handa, Sudhanshu; Angeles, Gustavo; Seidenfeld, David
Highlights: A program providing cash transfers and child support services in Zimbabwe reduces youth exposure to physical abuse. Physical violence among youth (aged 13 to 24 years) declines by 19 percentage points four years into the program. Improvements in household food security and caregiver subjective well-being could be channeling the reductions in violence. Abstract: Violence against children and adolescents, a highly prevalent problem, is a clear violation of child rights and has detrimental effects on later life outcomes. Programs that alleviate poverty address a structural determinant of child vulnerability and can thereby reduce child abuse. This paper investigates whether the Government of Zimbabwe's Harmonized Social Cash Transfer (HSCT) Program, which combines cash transfers with complementary services, affects youth exposure to physical violence. The analysis uses data from a non-experimental impact evaluation and a difference-in-differences approach. Results show a 19-percentage point decline in the incidence of physical violence among youth four years into the program. HSCT-induced enhancements in beneficiary households' purchasing capacity and food security, improvements in caregiver subjective well-being, and reductions in youth participation in economic work for pay could be mediating the program's effects on youth abuse. This paper adds to the relatively scarce evidence on the impacts of anti-poverty policies on young people's susceptibility to physical violence in developing countries.